Study the effects of adding crushed of Grape seeds (Vitis vinifera) in the diet to reduce the effect of heat stress on some physiological parameters broiler roosters (Hubbard flex). - Khafaji, Sura Safi (Journal of Kerbala for Agricultural Sciences, 2016)
Targeted research study the effect of adding crushed seed of grape (Vitis vinifera) on some biochemical parameters of broiler roosters (Hubbard flex). Thirty roosters, Twenty-sex weeks age, were randomly divided into three equal groups. First group (control) fed on the standard provender along the experimental period (10 weeks), second & third groups (T1& T2) fed on standard provender supplemented with 2.5 & 5 g/kg feed, respectively. At the end of experiment, blood samples were obtained from wing vein for estimation Total protein, albumin, globulin, cholesterol, testosterone, Follicle-stimulating Hormone (FSH) & Luteinizing Hormone (LH) concentrations in blood serum. The control treatment showed significant decrease in all physiological traits such as the level of total protein , globulin, testosterone, FSH & LH when compared with the poultry was consumed grape seeds in the diet from summer season, the above changes indicate the ability of heat stress in the induction of oxidative stress in broiler roosters. On the other hand, The result showed that crushed seed of grape supplementation in the two treated groups caused a significant increase (P<0.05) in total protein , globulin & cholesterol in two treated groups compared with control. Also, the elevation in albumin didn’t reach the significant level (P>0.05) in the comparison between the three groups.. The result of testosterone, FSH & LH showed a significant increment (P<0.05) in two treated groups compared with control.